KOMBINASI LA DAN FCO SEBAGAI PENGAMAN TRANSFORMATOR DISTRIBUSI DI PT. PLN (PERSERO) AREA BALI SELATAN - Adi Sumastra, I Putu; Dyana Arjana, I Gede; Rinas, I Wayan (Jurnal SPEKTRUM; Vol 8 No 4 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i04.p11, 2022)
The 20 Kv distribution network at Dewa Ruci has 61 distribution substations using the SUTM network with AAAC conductors 1 x 150 mm², because distribution substations are placed in the open, lightning surge disturbances and overloads that result in damaged transformers, transformers need protection against disturbances, so selected LA placement before and after FCO to protect the transformer from lightning surge interference with a fast 4/10 us wave propagation. Placement of LA before the FCO with a distance of 2 meters from the transformer there is a voltage increase of 89.3515748 kV with a working voltage of LA 87 kV for a LA protection factor of 95.7 kV, the possibility of LA failing to secure the transformer. Placement of LA after FCO with a distance of 0.3 meters from the transformer there is a voltage increase of 13.40273622 kV still at the working voltage and LA protection factor so that the transformer is still safe.